The Effectiveness of Public Speaking Learning Media Based on Digital Multimodal in Indonesian Language Courses at Politeknik Pariwisata Medan - Rachel Yoan Katherin Putri Siahaan; Syahnan Daulay; Wisman Hadi (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2020)
Digital media or often referred to as new media (new digital media) is an electronic media stored in digital format (as opposed to analog format) which can be used as storage, transmit, and receive digitalized information. Digital media is the internet-based media using computers and sophisticated mobile phones. Digital media as internet-based media has the characteristics of (1) computer-based technology; (2) its characteristics are hybrid, not dedicated, flexible; (3) interactive potential; (4) public and private functions; (5) non-strict regulations; (6) interrelation; (7) ubiquitous / independent of location; (8) can be accessed by individuals as communicators. (4) public and private functions; (5) non-strict regulations; (6) interrelation; (7) ubiquitous / independent of location; (8) can be accessed by individuals as communicators. (4) public and private functions; (5) non-strict regulations; (6) interrelation; (7) ubiquitous / independent of location; (8) can be accessed by individuals as communicators. This development research will be carried out at the Medan Tourism Polytechnic which is located at Jalan Rumah Sakit Haji No. 12, Kenanga Baru, Percut Sei Tuan District, and Deliserdang Regency. This Polytechnic has seven Study Programs, namely one Diploma 4 (D-4) Study Program and six Diploma 3 (D-3) Study Programs. The seven study programs are (1) D-4 Hospitality Management, (2) D-3 Room Division Management, (3) D-3 Food Management Management, (4) D-3 Catering Management, (5) D-3 Patiseri Management, (6) Tourism Planning and Marketing Management, and (7) D-3 Travel Tour. This digital multimodal-based public speaking learning media is very effective to use to improve learning outcomes. The learning outcomes after applying this product were at an average of 89.68%, meanwhile the learning outcomes before the application of learning media were at an average (55.93%).